Socio-political dimension of Merab Mamardashvili’s philosophy - Pustovit, Svitlana (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2024)
The paper focuses on the social and political aspects of the intellectual legacy of Georgian philosopher of the 1960s, Merab Mamardashvili. It is shown that his understanding of the political and social coincides with primary, ancient Greek understanding of citizen’s duty to take care of social welfare, to take an active part in the public life of the polis. The importance of socio-political dimension of philosopher’s intellectual legacy, as well as his discovery of metaphysical grounds of citizens’ political non-freedom under totalitarian regime, has been emphasized. According to Mamardashvili, social existence and justice require personality’s full presence as well as ongoing thinking and moral work; however, freedom, goodness and justice are quasi-object symbols and intelligible things born through the common experience of people’s existence in the conditions of civil society.